Diez narradores argentinos - Paola, Luis de ((Libro Amigo ;)
Contiene cuentos de Haroldo Conti, Antonio di Benedetto, Daniel Moyano, Juan José Saer, Juan José Hernández, Germán Rozenmacher, Vicente Battista, Abelardo Castillo, Rodolfo Walsh y Juan Carlos Martini.